1996
DOI: 10.1149/1.1837300
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Synthetic Graphite and Li Electrodes in Electrolyte Solutions Based on Ethylene Carbonate‐Dimethyl Carbonate Mixtures

Abstract: This work entails a comparative study of both Li and synthetic graphite electrodes in electrolyte solutions based on ethylene and dimethyl carbonates (EC-DMC) and the impact of the salt used [from the LiAsF,, LiC1O4, LiPF,, LiBF4, and LiN(SO2CF3)2 listi. The presence of some additives in solutions (e.g., Li2CO3, C02, tributylamine) and the effect of the particle size of the carbon on the electrode's behavior were investigated. The correlation between the surface chemistry, the morphology, and the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
552
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(572 citation statements)
references
References 9 publications
20
552
0
Order By: Relevance
“…Li 2 CO 3 is a product of EC reduction and has characteristic FTIR bands around 863 cm −1 and 1450 cm −1 . 63 Consistent with analysis of the C 1s and O 1s XPS spectra, FTIR also showed Li 2 CO 3 as an important component in the SEI. Features around 1100 cm −1 could be attributed to alkoxides like CH 3 OLi.…”
Section: A1842supporting
confidence: 69%
“…Li 2 CO 3 is a product of EC reduction and has characteristic FTIR bands around 863 cm −1 and 1450 cm −1 . 63 Consistent with analysis of the C 1s and O 1s XPS spectra, FTIR also showed Li 2 CO 3 as an important component in the SEI. Features around 1100 cm −1 could be attributed to alkoxides like CH 3 OLi.…”
Section: A1842supporting
confidence: 69%
“…Electrolyte salts dissolved in either THF or Et 2 6 could not be measured reliably by NMR spectroscopy. However, in all cases low concentrations of residual salt are observed after the reduction reactions and some of the reduction products may precipitate prior to complete reduction, so the number of electrons required for reduction of the different salts should be viewed as approximate.…”
Section: Resultsmentioning
confidence: 99%
“…13 Actually, significant evolution of gaseous products such as CO 2 , CO, O 2 , H 2 , CH 4 , C 2 H 4 , C 2 H 6 , C 3 H 6 and C 3 H 8 from the decomposition of carbonate solvents and lithium during battery operation has been detected by various characterization techniques. [14][15][16][17][18][19][20][21] In addition, utilizing isotope analysis, Onuk et al have unambiguously identified the origin of gases evolving in LIBs. 22 Furthermore, by adopting in situ transmission electron microscopy (TEM) 23 and neutron radiography (NR), 9,11 the generation of gaseous bubbles channels formed by the gas have recently been visualized.…”
Section: Introductionmentioning
confidence: 99%